Transmission of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) from pre and asymptomatic infected individuals: a systematic review. (February 2022) - Jefferson, Tom; Spencer, Elizabeth A.; Brassey, Jon; Onakpoya, Igho J.; Rosca, Elena C.; Plüddemann, Annette; Evans, David H.; Conly, John M.; Heneghan, Carl J.
Abstract: Background: The role of SARS-Cov-2-infected persons who develop symptoms after testing (presymptomatics) or not at all (asymptomatics) in the pandemic spread is unknown. Objectives: To determine infectiousness and probable contribution of asymptomatic persons (at the time of testing) to pandemic SARS-CoV-2 spread. Data sources: LitCovid, medRxiv, Google Scholar, and WHO Covid-19 databases (to 31 March 2021) and references in included studies. Study eligibility criteria: Studies with a proven or hypothesized transmission chain based either on serial PCR cycle threshold readings and/or viral culture and/or gene sequencing, with adequate follow-up. Participants: People exposed to SARS-CoV-2 within 2–14 days to index asymptomatic (at time of observation) infected individuals. Interventions: Reliability of symptom and signs was assessed within contemporary knowledge; transmission likelihood was assessed using adapted causality criteria. Methods: Systematic review. We contacted all included studies' corresponding authors requesting further details. Results: We included 18 studies from a diverse setting with substantial methodological variation (this field lacks standardized methodology). At initial testing, prevalence of asymptomatic cases was 12.5–100%. Of these, 6–100% were later determined to be presymptomatic, this proportion varying according to setting, methods of case ascertainment and population. Nursing/care home facilities reported high rates of presymptomatic: 50–100% ( n  = 3 studies). Fourteen studies were classified as high risk of, and four studies as at moderate risk of symptom ascertainment bias. High-risk studies may be less likely to distinguish between presymptomatic and asymptomatic cases. Six asymptomatic studies and four presymptomatic studies reported culturing infectious virus; data were too sparse to determine infectiousness duration. Three studies provided evidence of possible and three of probable/likely asymptomatic transmission; five studies provided possible and two probable/likely presymptomatic SARS-CoV-2 transmission. Conclusion: High-quality studies provide probable evidence of SARS-CoV-2 transmission from presymptomatic and asymptomatic individuals, with highly variable estimated transmission rates.